Determination of the Optical Properties of Cobalt Oxide Using Ultraviolet Visible Spectroscopy - Ahmed Elsammani , Ahmed Hashim; Gesmallah Ismail, Hasbalrasoul (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study explores the optical properties of cobalt oxide using ultraviolet-visible spectroscopy, crucial for applications in optical reagents, solar cells, and related technologies. Five samples with varying molarities (0.1, 0.3, 0.5, 0.7, and 0.9 M) of cobalt oxide were prepared via the Sol-Gel technique. Optical characteristics including absorption, reflection, refraction, transmission, absorption coefficient, and energy gap were analyzed using a Shimadzu 1240 scanning spectrophotometer at room temperature over a wavelength range of 273 to 585 nm. Key findings include a maximum absorbance of 1.02 within 273 to 351 nm, transmission value of 28% at 312 nm, and reflection value of 0.113 from 272 to 351 nm. The absorption coefficient peaked at 4.52 × 10³ within 273 to 351 nm, and the energy gap was determined as 3.782 eV at 368 nm, consistent with the expected range for conductor oxides (3.0 - 4.0 eV) within the wavelength range of 300 to 400 nm. The study reveals that increasing cobalt oxide concentrations, increases absorption and absorption coefficient and decreases reducing reflectance and energy gap. This research recommends further investigation using different concentrations of cobalt oxide and suggests employing alternative methods and devices for validating these optical property determinations on the same samples.